Interobserver variability in assessing dysplasia and architecture in colorectal adenomas: a multicentre Canadian study. Issue 9 (8th July 2014) - Osmond, Allison; Li-Chang, Hector; Kirsch, Richard; Divaris, Dimitrios; Falck, Vincent; Liu, Dong Feng; Marginean, Celia; Newell, Ken; Parfitt, Jeremy; Rudrick, Brian; Sapp, Heidi; Smith, Sharyn; et al.
Abstract : Aims: Following the introduction of colorectal cancer screening programmes throughout Canada, it became necessary to standardise the diagnosis of colorectal adenomas. Canadian guidelines for standardised reporting of adenomas were developed in 2011. The aims of the present study were (a) to assess interobserver variability in the classification of dysplasia and architecture in adenomas and (b) to determine if interobserver variability could be improved by the adoption of criteria specified in the national guidelines. Methods: An a priori power analysis was used to determine an adequate number of cases and participants. Twelve pathologists independently classified 40 whole-slide images of adenomas according to architecture and dysplasia grade. Following a wash-out period, participants were provided with the national guidelines and asked to reclassify the study set. Results: At baseline, there was moderate interobserver agreement for architecture (K=0.4700; 95% CI 0.4427 to 0.4972) and dysplasia grade (K=0.5680; 95% CI 0.5299 to 0.6062). Following distribution of the guidelines, there was improved interobserver agreement in assessing architecture (K=0.5403; 95% CI 0.5133 to 0.5674)). For dysplasia grade, overall interobserver agreement remained moderate but decreased significantly (K=0.4833; 95% CI 0.4452 to 0.5215). Half of the cases contained high-grade dysplasia (HGD). Two pathologists diagnosed HGD in ≥75% of cases. Conclusions: The improvement in interobserver agreement in classifying adenoma architecture suggests that national guidelines can be useful in disseminating knowledge, however, the variability in the diagnosis of HGD, even following guideline review suggests the need for ongoing knowledge-transfer exercises.